Inland primary fisheries cooperative societies in Tamil Nadu: current status and support mechanisms - DINESH, RAJAN; ARGADE, SHIVAJI; JANARTHANAN , GUNASEKARAN; SEENIVASAN, PERIYASAMY (Journal of the Inland Fisheries Society of India, 2025)
The Inland Primary Fisheries Cooperative Societies (IPFCSs) play a crucial role in improving inland fishers’ livelihoods in Tamil Nadu, acting as key intermediaries for distributing various welfare schemes to support the fishing community. The study assessed the status and institutional support for IPFCSs, using data from the Tamil Nadu State Apex Fisheries Cooperative Federation Limited (TAFCOFED), Tamil Nadu Fishermen Welfare Board (TNFWB), Tamil Nadu Fisheries policy note (2014-2022) and interactions with TAFCOFED officials. The results revealed that Tamil Nadu has the highest cooperative membership in India, with 7,61,521 (19.19%) active members, of which 90,869 (11.87%) are inland fishers across 372 IPFCSs. From 2014 to 2022, the IPFCSs’ Compound Annual Growth Rate (CAGR) was 0.10%, with inland fisherwomen cooperatives growing at 1.09% while inland fishermen cooperatives saw a slight decline (-0.12%). The northern and northeastern districts, particularly Tiruvannamalai (32), Cuddalore (31), Viluppuram (28), and Thiruvallur (26) have the most IPFCSs, Meanwhile, Mayiladuthurai (1), along with Ramanathapuram and Ariyalur, both with 2 societies each, highlights areas where cooperative efforts appear to be underdeveloped. A total of 81,813 cooperative members, representing 90.03% of the total membership, are actively engaged in fishing activities, with 74,708 active members in fishermen cooperatives compared to only 7,105 in fisherwomen cooperatives. Pearson correlation analysis showed significant relationships between inland fish production and the availability of inland water resources (r = 0.685, p < 0.01), highlighting the crucial role of water management in enhancing fish production. However, there is a weak and insignificant relationship between fish production and both the number of inland fisheries cooperatives (r = 0.112, p = 0.542) and active membership (r = 0.170, p = 0.353), suggesting that cooperatives, while important for an organization, do not directly influence the inland fish production. TAFCOFED implements various schemes to further support and promote fishing cooperatives in Tamil Nadu. These initiatives encompass the supply of fish transport vehicles, the provision of subsidized fishing inputs, and the construction of fish markets. Additionally, the TNFWB supplements offer various welfare schemes and support to IPFCSs.